The Small Ruminants of West Africa - A Review - Ngere, L.O. (OAU, 1985)
Paper presented at the expert committee meeting on animal genetic resources in Africa, 1983. The small ruminants of West Africa constitute an important genetic resources for the region, with great potential for contributing to the protein nutrition and sufficiency in the region. Topical discussion included general introduction, livestock numbers in the region, small ruminants productivity and its constraints, disease and future prospects.